2019
DOI: 10.1111/jphp.13208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on Aβ1–42-induced alteration of SESN2, SIRT1, LC3II and TPP1 protein expressions in neuronal cell cultures

Abstract: Objectives Sestrins (SESNs) and sirtuins (SIRTs) are antioxidant and antiapoptotic genes and crucial mediators for lysosomal autophagy regulation that play a pivotal role in the Alzheimer's disease (AD). Recently, statins have been linked to the reduced prevalence of AD in statin-prescribed populations yet molecular basis for the neuroprotective action of statins is still under debate. Methods This study was undertaken whether Ab-induced changes of SESN2 and SIRT1 protein expression, autophagy marker LC3II and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 97 publications
(227 reference statements)
2
20
0
Order By: Relevance
“…He based his conclusions on the results of studies that showed that COX-1 inhibitors with anti-inflammatory effects slow down cognitive decline while reducing Ab platelets [22]. Sun and colleagues also came to the same conclusions, who showed that the amyloid-beta solution induces an increase in TNF-alpha and IL-6 levels [16]. Moreover, the amyloid b peptide has been shown to increase microglia activation by increasing the production of inflammatory cytokines interleukin-1b (IL-1b), interleukin-6 (IL-6) and tumor necrosis factor a (TNF-a) [30].…”
Section: How Do Statins Work On Risk Factors For Alzheimer's?mentioning
confidence: 91%
See 3 more Smart Citations
“…He based his conclusions on the results of studies that showed that COX-1 inhibitors with anti-inflammatory effects slow down cognitive decline while reducing Ab platelets [22]. Sun and colleagues also came to the same conclusions, who showed that the amyloid-beta solution induces an increase in TNF-alpha and IL-6 levels [16]. Moreover, the amyloid b peptide has been shown to increase microglia activation by increasing the production of inflammatory cytokines interleukin-1b (IL-1b), interleukin-6 (IL-6) and tumor necrosis factor a (TNF-a) [30].…”
Section: How Do Statins Work On Risk Factors For Alzheimer's?mentioning
confidence: 91%
“…However, due to their pleiotropic effect, we should not limit their use. Experimental studies have shown that statins reduce Ab production, inhibit inflammatory reactions, protect neurons from neurotoxicity induced by pathological protein, and oxidative stress [8,16]. We divide statins according to their properties.…”
Section: Statins Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…On these premises, the first aim of this work is to fully characterize, by using a pharmacological approach, the differential regulation of the HO/BVR system by both sAβ and fAβ in the human neuroblastoma SH-SY5Y cells, a reliable experimental system widely used to study neurodegeneration and AD ( Marrazzo et al, 2019 ; Wang et al, 2019 ; Celik et al, 2020 ). Furthermore, since in vivo data have shown that the COX-2 inhibitor celecoxib (CXB) reduces neuroinflammation and prevents cognitive impairment and behavioral abnormalities in sAβ-treated rats, the second aim of this work is to investigate whether or not CXB modulates the HO/BVR system in SH-SY5Y cells, thus widening the spectrum of its therapeutic activity.…”
Section: Introductionmentioning
confidence: 99%